Comparative proteomic analysis reveals the pathological mechanisms of overuse achilles tendinopathy and the therapeutic mechanisms of ESWT and PRP - Gongzi Zhang; Tianshu Zhao; Yangxiaoxue Liu; Jianing Xu; Wenxi Luo; Hao Liu; Bei Liu; Jingxian Hou; Jiali Zhang; Ruining Wu; Ming Zhou; Liping Huang (Tissue and Cell, 2026)

A two-dimensional nanocatalytic engineered saliva immunosensor for acute myocardial infarction high-sensitivity detection - Jingyi Yang; Lei Li; Xuanyu Xiao; Yuting Zhong; Zetai Zheng; Yue Zhou; Tianshu Wang; Chenxu Wang; Wei Deng; Chenjun Xu; Chen Li; Qinsheng Hu; et al. (Chemical Engineering Journal, 2026)

NtWHY1 negatively regulates tobacco cold tolerance via interfering with flavonoid biosynthesis - Zhen Gao; Qingxia Zheng; Leyu Zhang; Xiao Wei; Tianshu Kou; Hui Zhang; Guoyun Xu; Hongxiang Tan; Xiaokun Guo; Huina Zhou; Yuntao Fan; Niu Zhai (Plant Cell Reports, 2026)

Ammonium may emerge as the primary driver of future aerosol acidity, replacing the historical role of sulfate over the coastal area of North China: Insights from a megacity (Qingdao) - Wenshuai Li; Yaoyu Song; Tianshu Chen; Yuxuan Qi; Guanru Wu; Xinshuo Wang; Wenwen Xie; Lifang Sheng; Wencai Wang; Wenjun Qu; Yang Zhou (Atmospheric Environment, 2026)

Reinforcement learning-based path planning for underwater gliders using ocean current forecasts - Yatao Zhou; Yang Li; Rongshun Juan; Tianshu Wang; Zezhong Li; Shoufu Liu; Wei Ma; Zhongke Gao (Ocean Engineering, 2026)

Carbon footprint of a traditional Chinese distilled spirit (Baijiu) with high-resolution supply-chain mapping - Hao Lu; Yisen Qian; Lyujun Chen; Wei Zhou; Kun Yan; Tianshu Ji; Yongtao Tang; Jinping Tian (Resources, Conservation and Recycling, 2026)

Event-triggered model predictive control for trajectory tracking of underwater gliders in currents - Tianshu Wang; Rongshun Juan; Man Luo; Jin Chen; Yang Li; Yatao Zhou; Zhongke Gao (Ocean Engineering, 2026)

Long-range straight-line path tracking for underwater gliders using reinforcement learning and ocean current forecasts - Yatao Zhou; Rongshun Juan; Yang Li; Tianshu Wang; Wei Guo; Ming Yang; Zhongke Gao (Ocean Engineering, 2025)

Comparison of the polluted dust plume and natural dust air mass in a spring dust event in Beijing 2023 - Zhenyi Chen; Zhonghao Zhou; Chengli Ji; Zhiliang Yao; Jiajia Mao; Zhicheng Wang; Yan Xiang; Tianshu Zhang; Yi Zhou; Zijian Chen; Gang Dou (Journal of Environmental Sciences, 2025)

Study on the characteristics of precipitation particle size distribution during freezing weather in the southwest mountainous areas of China - Haopeng Wu; Shengjie Niu; Seong Soo Yum; Jingjing Lü; Chunsong Lu; Yue Zhou; Jing Sun; Yixiao He; Tianshu Wang; Xinyi Wang (Science China Earth Sciences, 2025)

Insights into the environmental–economic sustainability of rice production in China - Liyao Wang; Tianzuo Zhang; Xinying Zhou; Tianshu Xu; Changting Li; Ziheng Li; Shuo Wang; Mengqing Li; Jinglan Hong (Journal of Cleaner Production, 2025)

Sensor array and color-coded test paper tongue based on multivariate cross-responsive AIEgen functionalized bimetallic lanthanide infinite coordination polymers: Toward smart identification and systematic analysis of antibiotics - Junxuan Zhu; Yuanyue Wu; Chenyi Xue; Manman Zhang; Yiling Zhang; Xuefei Zhang; Tianshu Zhou; Jingjing Deng (Chemical Engineering Journal, 2024)

Sustainability assessment for China's intensive dairy farming: Integrating environmental and economic perspectives - Tianshu Xu; Tianzuo Zhang; Ziyue Cheng; Ziheng Li; Shuo Wang; Xinying Zhou; Changting Li; Liyao Wang; Mengqing Li; Jinglan Hong (Sustainable Production and Consumption, 2024)

High-precision motion control of underwater gliders based on reinforcement learning - Rongshun Juan; Tianshu Wang; Shoufu Liu; Yatao Zhou; Wei Ma; Wendong Niu; Zhongke Gao (Ocean Engineering, 2024)

Carbon–water–energy footprint impacts of dyed cotton fabric production in China - Changting Li; Tianzuo Zhang; Xinying Zhou; Ziyue Cheng; Tianshu Xu; Ziheng Li; Jinglan Hong (Journal of Cleaner Production, 2024)

Promoting sustainable potato production - Insights from an integrated life cycle environmental–economic assessment - Tianzuo Zhang; Changting Li; Shuo Wang; Ziyue Cheng; Ziheng Li; Tianshu Xu; Xinying Zhou; Wei Chen; Jinglan Hong (Agricultural Systems, 2024)

Rational fabrication of Z-scheme heterojunction ZnFe2O4-seed@TpTt-COF for the visible-light-driven photocatalytic degradation of bisphenol A in food waste leachate boosted by primitive humic acid - Manman Zhang; Huihan Cao; Min Wu; Yiling Zhang; Junxuan Zhu; Juan Xu; Jingjing Deng; Tianshu Zhou (Chemical Engineering Journal, 2024)

Hazard or Non-Hazard Flood: Post Analysis for Paddy Rice, Wetland, and Other Potential Non-Hazard Flood Extraction from the VIIRS Flood Products - Donglian Sun; Tianshu Yang; Sanmei Li; Mitchell Goldberg; Satya Kalluri; Sean Helfrich; Bill Sjonberg; Lihang Zhou; Qingyuan Zhang; William Straka; Ruixin Yang; Fernando Miralles-Wilhelm (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Uncovering the energy-carbon-water footprint of waste rubber recycling: Integrated environmental and economic perspectives - Xinying Zhou; Yijie Zhai; Tianzuo Zhang; Ziheng Li; Ziyue Cheng; Changting Li; Tianshu Xu; Jinglan Hong (Journal of Environmental Management, 2023)

Ultrafast and facile construction of programmable, multidimensional wrinkled-patterned polyacrylamide/sodium alginate hydrogels for human skin-like tactile perception - Jianhua Huang; Gong Chen; Tianhang Han; Chenxin Yi; Yujia Zhang; Lang Ding; Tianshu Sun; Ting Jin; Shuai Zhou (Carbohydrate Polymers, 2023)

Life cycle environmental and cost assessment of prefabricated components manufacture - Ziyue Cheng; Tianzuo Zhang; Xinying Zhou; Ziheng Li; Yuke Jia; Ke Ren; Tianshu Xu; Changting Li; Jinglan Hong (Journal of Cleaner Production, 2023)

A facile rapid-response and on-site sensor for tetracycline detection in environmental water based on europium-doped carbonized polymer dots - Qi Nie; Jingjing Deng; Tianshu Zhou (Journal of Environmental Chemical Engineering, 2023)

One-step in situ construction of anisotropic bilayer hydrogel with high sensitivity and wide detection range for adaptive tactile sensing - Lujing Wang; Yangrong Peng; Jingtong Liu; Chenxin Yi; Tianhang Han; Lang Ding; Zhenyang Luo; Tianshu Sun; Shuai Zhou (Chemical Engineering Journal, 2023)

How can ecosystem status be more comprehensively reflected? A case study of Jinan City, China - Ziheng Li; Yijie Zhai; Tianzuo Zhang; Xinying Zhou; Ziyue Cheng; Tianshu Xu; Changting Li; Jinglan Hong (Science of The Total Environment, 2023)

Retrieval of tropospheric ozone profiles using ground-based MAX-DOAS - Yuanyuan Qian; Yuhan Luo; Ke Dou; Haijin Zhou; Liang Xi; Taiping Yang; Tianshu Zhang; Fuqi Si (Science of The Total Environment, 2023)

Changes in the m6A RNA methylome accompany the promotion of soybean root growth by rhizobia under cadmium stress - Xue Han; Jialin Wang; Yu Zhang; Youlin Kong; Huiying Dong; Xuezhen Feng; Tianshu Li; Changjun Zhou; Jidong Yu; Dawei Xin; Qingshan Chen; Zhaoming Qi (Journal of Hazardous Materials, 2023)

miR-146a contributes to atherosclerotic plaque stability by regulating the expression of TRAF6 and IRAK-1 - Tianshu Chu; Xu Xu; Zhimin Ruan; Liyong Wu; Mingli Zhou; Guofu Zhu (Molecular Biology Reports, 2022)

Localization of QTL for cold tolerance at the germination stage of rice (Oryza sativa L.) using recombinant inbred lines - Liangzi Cao; Shukun Jiang; Guohua Ding; Tongtong Wang; Liangming Bai; Jinsong Zhou; Yu Luo; Tianshu Xia; Hui Jiang; Kai Liu; Xueyang Wang; Guang Yang; et al. (Genetic Resources and Crop Evolution, 2022)
The cold tolerance of germinating direct-sown rice ( Oryza sativa L.) has an increased rate of emergence, which ensures vigorous seedling growth. Research on QTL localization for cold tolerance at the germination stage can assist in molecular marker-assisted selection and enhance breeding efficiency. In this study, 94 populations of recombinant self-incompatible lines from Heigu and Ha 9366 were selected to investigate germination rates at low temperatures. It was found that two QTL loci (qLTG-3 and qLTG-12) were located at different germination times on chromosomes 3 and 12, respectively. The two QTLs at three different germination times, located using QTL, accounted for 21.3–25.9% of the phenotypic variation. Moreover, a reciprocal effect was detected between the two QTLs. The double QTLs increased the germination rate by 22–27% in this population. Additionally, qLTG-12 improved cold tolerance at the seedling stage. The results of this study might provide the materials and molecular markers for future molecular marker-assisted breeding for cold tolerance at the germination stage.

JNK-dependent phosphorylation and nuclear translocation of EGR-1 promotes cardiomyocyte apoptosis - Jinrun Zhou; Yujuan Yao; Jiaojiao Zhang; Zhaohui Wang; Tianshu Zheng; Yao Lu; Weihua Kong; Jing Zhao (Apoptosis, 2022)

miR-155 inhibits oxidized low-density lipoprotein–induced apoptosis in different cell models by targeting the p85α/AKT pathway - Zhimin Ruan; Tianshu Chu; Liyong Wu; Mingguo Zhang; Mei Zheng; Qian Zhang; Mingli Zhou; Guofu Zhu (Journal of Physiology and Biochemistry, 2020)

Observational Study on the Supercooled Fog Droplet Spectrum Distribution and Icing Accumulation Mechanism in Lushan, Southeast China - Tianshu Wang; Shengjie Niu; Jingjing Lü; Yue Zhou (Advances in Atmospheric Sciences, 2019)

Microsatellite records for volume 8, issue 2 - Dareen Almojil; Maria Cristina Arias; Rochelle R. Beasley; Yiyong Chen; Rulon W. Clark; Yinghui Dong; Zhiguo Dong; Natalie Forsdick; Elaine Françoso; E. González-Ortegón; A. M. González-Tizón; Linsheng Gui; et al. (Conservation Genetics Resources, 2016)

Effect of Iodine Excess on Th1, Th2, Th17, and Treg Cell Subpopulations in the Thyroid of NOD.H-2h4 Mice - Xiao Yang; Tianshu Gao; Rui Shi; Xiyu Zhou; Jinqiao Qu; Jia Xu; Zhongyan Shan; Weiping Teng (Biological Trace Element Research, 2014)